2002
DOI: 10.1063/1.1494466
|View full text |Cite
|
Sign up to set email alerts
|

Formation of pnp bipolar structure by thermal donors in nitrogen-containing p-type Czochralski silicon wafers

Abstract: Oxygen precipitation in nitrogen doped Czochralski silicon wafers. I. Formation mechanisms of near-surface and bulk defects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The mechanism of N-doping on oxygen precipitation in lightly doped CZ-Si has been well documented [7][8][9][10][11][12], about which a short review is addressed as following. Generally, it is believed that N-N pairs are formed in NCZ-Si approximately at the melting temperature [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of N-doping on oxygen precipitation in lightly doped CZ-Si has been well documented [7][8][9][10][11][12], about which a short review is addressed as following. Generally, it is believed that N-N pairs are formed in NCZ-Si approximately at the melting temperature [20].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, enhancing oxygen precipitation in heavily P-doped CZ-Si becomes necessary. Up to the present time, it is well documented that nitrogen co-doping is an effective pathway to enhance oxygen precipitation in CZ-Si [7][8][9][10][11][12]. Then, whether this scenario is also the case for heavily P-doped CZ-Si it is an interesting issue to be investigated.…”
Section: Introductionmentioning
confidence: 97%
“…It has been well accepted that nitrogen doping can enhance oxygen precipitation and thus improve the IG capability of Cz-Si wafers. The IG structures for NCZ-Si wafer could be easily achieved by high-low-high temperature (Hi-Lo-Hi) three-step anneal [14], or by hightemperature anneal ramping-up from low temperature [15] or even by single-step high-temperature anneal [16]. Shimura et al [17] have reported that tiny oxygen precipitates might exist in the oxygen out-diffusion zone of NCZ-Si after Hi-Lo-Hi treatments, which would affect the quality of DZ.…”
Section: Nitrogenmentioning
confidence: 99%
“…It has been well proved that the doping of nitrogen into Czochralski (CZ) silicon results in manifold advantageous effects as follows: (1) reducing the size of voids in the silicon so that the voids can be annihilated at lower temperature [1]; (2) enhancing oxygen precipitation and therefore the intrinsic gettering capability [2][3][4][5]; (3) increasing the mechanical strength of the CZ silicon wafer, which is beneficial in reducing the warpage of the wafer during device processing [6,7]. The contemporary advanced device processes that adopt the CZ silicon wafers with diameters of 200 mm and above are moving towards low initial oxygen concentration ([O i ]) and thermal budgets.…”
Section: Introductionmentioning
confidence: 99%